2017
DOI: 10.1155/2017/9718615
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Decreased Acetylcholinesterase Activity at the Neuromuscular Junction of the Diaphragm during Sepsis

Abstract: Our recent study demonstrated that acetylcholinesterase (AChE) activity at the neuromuscular junction (NMJ) of the diaphragm decreased during sepsis. However, the mechanisms were not clearly identified. In this study, we aimed to investigate whether the decreased AChE activity was related to oxidative stress by observing AChE activity in different grades of sepsis induced by caecal ligation and puncture (CLP). At 24 h after surgery, an assay of thiobarbituric acid reactive species (TBARS) and protein carbonyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…Previous work on aged GI tract has shown an increase in reactive oxygen species in animal models with increasing age, although similar changes in the humans have not been so clearly documented . Oxidative stress has also been demonstrated to reduce cholinesterase activity in a range of tissues providing a potential mechanism for changes observed in this study …”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous work on aged GI tract has shown an increase in reactive oxygen species in animal models with increasing age, although similar changes in the humans have not been so clearly documented . Oxidative stress has also been demonstrated to reduce cholinesterase activity in a range of tissues providing a potential mechanism for changes observed in this study …”
Section: Discussionsupporting
confidence: 50%
“…40 Oxidative stress has also been demonstrated to reduce cholinesterase activity in a range of tissues providing a potential mechanism for changes observed in this study. [41][42][43] About 1 μmol L −1 physostigmine has been shown to completely block cholinesterase activity in other GI tract smooth muscles.…”
Section: Changes In Purinergic Signaling Across the Lifecoursementioning
confidence: 99%
“…Muscle relaxant antagonists exert their therapeutic effect by inhibiting AChE activity, which causes more acetylcholine release and ultimately accelerates muscle function restoration [12]. Our previous study verified that AChE activity decreased at the NMJ in the diaphragm during sepsis and oxidative stress was a vital contributor [13]. Drugs could inhibit the inflammation, and/or oxidative stress is theoretically useful for maintaining diaphragmatic contractile function and AChE activity during sepsis.…”
Section: Introductionmentioning
confidence: 68%
“…(25)(26)(27)(28)(29)(30) It is demonstrated that sepsis induced by both gauge 18 and gauge 21can elevate ROS levels in the liver, colon and kidney 16 to 24 hours following the procedure (31)(32)(33)(34). In addition, 6 to 48 hours after the procedure, LPO level, increases in the lung, ileum, diaphragm, heart, brain and kidney (regardless of the gauges used) (26)(27)(28)(29)(30)(34)(35)(36)(37)(38)(39)(40)(41). Congruently, the ndings of our study demonstrated that 24 hours after the CLP procedure, in both cardiac and pulmonary tissues, oxidative stress markers increased, whereas the levels of antioxidant indicators reduced in comparison with the sham group.…”
Section: Discussionmentioning
confidence: 99%